(untitled) (ENTHYMEMA, 2024)
The essay consists of two independent yet intimately connected sections. It investigates two different aspects of Primo Levi’s work. The former one focuses on the conceptual categories of ’seeing’ and ’inventing’ in the creative process of literary ’creation’, which takes the form of a rhetorical operation of inventio and dispositio of punctiform intuitions. The latter inquires the role played by empathy in Primo Levi’s works.